From On-Campus to Online: A Trajectory of Innovation, Internationalization and Inclusion - Moreira, Darlinda (International Review of Research in Open and Distributed Learning, 2016)
This paper presents a study focused on a trajectory for developing an online operating mode on a campus-based university in the area of Massachusetts, USA. It addresses the innovation process and the changes and challenges faced by faculty and administrators. Methodologically-speaking, a mainly ethnographic approach was used for a systematic process of collecting data in context, in order to understand organizational strategies put in place to launch and improve online course provision. Leaders of the process and teachers of online courses were also interviewed. What emerged was: a) the online operating mode was prepared much in advance and linked to scenarios of internationalization and inclusion in higher education; b) there was an underlying discourse of inter-connectedness among different places and groups of people; and c) the partnership and collaboration between administration and faculty was essential. One of the main conclusions demonstrates that, despite careful formulation of the online component, it still does not enjoy the same status as the face-to-face element of courses, and, as a result, is largely ignored in terms of promotion in the teaching profession.